The relationship between university students’ quality of life and nutrition - Dalbudak, İbrahim and Yiğit, Şıhmehmet and Yılmaz, Taner (Progress in Nutrition, 2020)
The aim of this study is to investigate whether there is a difference in nutrition habits of the students in different departments of a vocational school in a university, depending on the life quality of them, and to compare by various variables. A total of 205 students, as 92 female and 113 male in Atabey Vocational School in Isparta University of Applied Sciences in the 2018-2019 academic year, participated in this study. Students who took or did not take the lesson of healthy life and nutrition, participated in the study. As a data collection tool in the research; the turkish version of The World Health Organization Quality of Life Scale short form questionnaire and, Three-factor Eating Questionnaire (TFEQ) were applied. And The Personal information Form was used to obtain the demographic information. In this study, SPSS 22.00 Programme was used which is used in quantitative research methods. The data were summarized by giving the percentage and frequency tables. Statistically, there are both significant (p < .05) and nonsignificant (p > .05) differences in students between life quality and its subfactors by age, gender, being engaged in sports, taking the lesson of healthy life and nutrition and income status. Since age and gender variables have no effect on any of the nutrition scale snd its sub-factors, there is no significant difference between them (p > .05). There is a significant difference between the students’ income level, the status of being actively involved in sports, the status of taking the lesson of healthy life and nutrition, and the nutrition scale and its sub-factors ( p < .05). Statistically, there was found a significant relationship intensive and in a positive way between individuals’ quality of life and their nutrition habits (p < .05). As the total score of the life quality scale or the total score of the nutrition scale increases, other one increases, as well. As a result, an increment in a significance level is observed in the quality of life and nutritional levels of the university students taking the lesson of healthy life and nutrition. When the lesson of healthy life and nutrition becomes a compulsory course and its length gets increased, we can say that there will be difference in the levels of the quality of life and nutrition. As a result of ensuring the participation in the class of healthy life and nutrition, we can say that it will be helpful for individuals in terms of protecting against disesases and gaining health life and nutrition behaviors by struggling against the factors that affect the life negatively. Since it will be useful to repeat this study in different fields as more inclusively, we can say that this study will shed light on future studies.